2019
DOI: 10.1177/0019793919852926
|View full text |Cite|
|
Sign up to set email alerts
|

Unions and Non-Standard Work: Union Representation and Wage Premiums across Non-Standard Work Arrangements in Canada, 1997–2014

Abstract: The authors examine the association between unionization and non-standard work in terms of coverage and wages. They use data from the master files of Canada’s Labour Force Survey (LFS) between 1997–98 and 2013–14 to define and measure non-standard work and to provide a continuum of vulnerability across work arrangements. The estimated probability of being employed in some form of non-permanent job increased 2.9 percentage points from 1997 to 2014. During that same period, the estimated probability of being in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This effective ‘0’ union wage premium in a model richly specified with right‐hand side conditioning variables is in line with models estimated using panel data and/or selection effects. Moreover, recent estimates in Canada (Campolieti, 2018 ; Gomez & Lamb, 2019 ) and elsewhere (Blanchflower & Bryson, 2010 ) have documented the decline of the union wage premium for the average worker. However, that same research has shown is that the union wage premium differs considerably among occupations (Blanchflower & Bryson, 2010 ) and by sub‐groups, especially among workers traditionally disadvantaged in the workplace (Gomez & Lamb, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effective ‘0’ union wage premium in a model richly specified with right‐hand side conditioning variables is in line with models estimated using panel data and/or selection effects. Moreover, recent estimates in Canada (Campolieti, 2018 ; Gomez & Lamb, 2019 ) and elsewhere (Blanchflower & Bryson, 2010 ) have documented the decline of the union wage premium for the average worker. However, that same research has shown is that the union wage premium differs considerably among occupations (Blanchflower & Bryson, 2010 ) and by sub‐groups, especially among workers traditionally disadvantaged in the workplace (Gomez & Lamb, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, that same research has shown is that the union wage premium differs considerably among occupations (Blanchflower & Bryson, 2010 ) and by sub‐groups, especially among workers traditionally disadvantaged in the workplace (Gomez & Lamb, 2016 ). It appears that workers who already have substantial labour market leverage benefit less from union coverage, whereas workers with less market power benefit more (Gomez & Lamb, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…They improve wages and job security, advocate for educational and training programs, limit precarious employment, and increase worker say within organizations. When unions engage with precarious workers and those in non-standard work arrangements (arrangements that often contain a disproportionate share of individuals from historically marginalized groups), they significantly improve those workers' earnings (Gomez and Lamb 2019).…”
Section: Resultsmentioning
confidence: 99%
“…They have also slightly shifted over time (Doellgast et al, 2018; Heery, 2009). Research examining social partners’ joint responses in Denmark (Larsen and Mailand, 2018), France (Simms et al, 2018), Australia (Markey and McIvor, 2018) and Canada (Gomez and Lamb, 2019) indicates there has been a shift from trying to overlook or exclude the interests of non-full-time permanent employees, towards acknowledging, organising and jointly pushing to regulate the conditions of these groups through collective bargaining or statute in order to limit discrimination and avoid unfair competition with full-time permanent employees.…”
Section: Research Problem and Conceptual Modelmentioning
confidence: 99%